(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Buildings undergo a lot of vibrations at the time of earthquakes or strong winds acting upon it. These vibrations make the building more prone to damages and create a sort of fear psychosis among the people residing in it. Thus, buildings need to be first analyzed for these vibrations, so as to design the building in such a way that its vibrations produced are minimized to a large extend, thereby eliminating the fear psychosis of people and making the building safer. High rise buildings undergo much more vibrations and lateral drifts as compared to low height buildings. Thus tall buildings are provided with shear walls to counteract and minimize the effect of lateral loads acting on the structure. The properties of these seismic shear walls dominate the response of the buildings, and therefore, it is important to evaluate the seismic response of the walls appropriately. In this present study, main focus is to determine the solution for shear wall location in high rise building and to cater the vibrations of the buildings produced due to lateral loading acting on the floors. In this project dynamic behavior of the building is to be studied carefully, so as to reduce the lateral drifts produced in the building and thus making the building resistant to the lateral loads. STAAD-Pro V8i software will be used to perform allthe parametric study analysis of these lateral loads upon the structure. Complicated and high-rise structures need very time taking and cumbersome calculations using conventional manual methods. STAAD-Pro provides us a fast, efficient, easy to use and accurate platform for analysing and designing structure. In this study different models were studied on the basisof different positions of shear walls, out of which model 4 (with lift core wall and shear wall at corners) showed better performance in regarding all the parameters of study which included storey drifts, base shear, frequency and axial forces. Two methods were taken for the analysis out of which response spectrum method showed better and precise results.